PRELIMINARY STUDY: FEEDING ECOLOGY AND DAILY ACTIVITY OF THREE COLORED LANGUR (Presbytis chrysomelas ssp cruciger Thomas, 1892) IN DANAU SENTARUM NATIONAL PARK - Santoso, Nyoto; Sutopo; Meo, Lorenzo Elton; Fauziah, Natasya Nurul; Diva, Alfatheya Margwita (SEAMEO BIOTROP, 2023)
Three colored langur (Presbytis chrysomelas ssp cruciger Thomas, 1892) is a primate that has been recognized as a critically endangered species in accordance with the International Union for Conservation of Nature, however still not protected and lacks substantial information about the bio-ecology of their natural habitat. The habitat plays a determining factor not only in space utilization but also the daily activities of the three colored langurs (P c cruciger). The aim of this preliminary study is to collect information regarding their habitat characteristic, feed species, daily activity, and canopy stratum utilization. This research was conducted between July and August of 2021 at Bukit Semujan, Lupak Mawang Resort, Danau Sentarum National Park. The method implemented was to collect the habitat characteristic by plot samples, and their daily activity data by scan sampling with consecutive recording. The study demonstrated that langur inhabited both primary as well as mixed forests (swamp, cultivation land, and secondary forest). There were 27 species as feeds of langurs and the most preferred types of feed are Gita susu (Willughbeia coriacea), Merepat (unidentified), and Karet (Hevea brasiliensis). The most preferred feed compositions consisted of leaves (50%), fruits (30%), and seeds (20%). The most frequently utilized stratum for activities was stratum C (70,49%) and B (27.87%). The highest daily activities were categorized into three parts of time, the morning was dominated by social (44,26%), the afternoon was dominated by rest (59,7 7%), and the evening was dominated by social (73,68%). The highest social activities shown by three colored langurs were agonistic (48,48%), followed by vocalization (39,39%), playing (10,61%), exploring (1,52%), and sexual (0%).